2022
DOI: 10.3390/jcdd9070217
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Epicardial Adipose Tissue in the Development of Atrial Fibrillation, Coronary Artery Disease and Chronic Heart Failure in the Context of Obesity and Type 2 Diabetes Mellitus: A Narrative Review

Abstract: Cardiovascular diseases (CVDs) are a significant burden globally and are especially prevalent in obese and/or diabetic populations. Epicardial adipose tissue (EAT) surrounding the heart has been implicated in the development of CVDs as EAT can shift from a protective to a maladaptive phenotype in diseased states. In diabetic and obese patients, an elevated EAT mass both secretes pro-fibrotic/pro-inflammatory adipokines and forms intramyocardial fibrofatty infiltrates. This narrative review considers the propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 139 publications
0
14
0
Order By: Relevance
“…Epicardial adipose tissue modulates the secretion of adipokines, molecules with an active role in the development of atherosclerosis [ 7 , 31 , 32 ]. In our study, we did not find statistically significant correlations between serum adipokine levels and epicardial adipose tissue thickness, but we attribute this result to the analysis of a small group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Epicardial adipose tissue modulates the secretion of adipokines, molecules with an active role in the development of atherosclerosis [ 7 , 31 , 32 ]. In our study, we did not find statistically significant correlations between serum adipokine levels and epicardial adipose tissue thickness, but we attribute this result to the analysis of a small group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The former is located directly around or on the coronary artery adventitia; the latter is located just over the myocardium and is in direct contact with the myocardium ( 9 ). Vascular supply by coronary arteries in EAT forms part of the perivascular adventitia ( 10 ). It is thought to play a protective mechanical role against the tension and twist of an arterial pulse ( 11 , 12 ).…”
Section: Epicardial Adipose Tissue: Anatomy and Physiologymentioning
confidence: 99%
“…Many observational studies have reported that increased epicardial is associated with adverse metabolic profile, cardiovascular risk factors, and coronary atherosclerosis in patients with cardiovascular diseases and in general population [1]. We and others have previously reported the independent association of increased epicardial fat with left ventricular (LV) hypertrophy and diastolic dysfunction as well as the development of heart failure (HF) and coronary artery disease in these populations [2][3][4][5][6][7][8]. In some studies, however, the association did not reach statistical significance [9,10].…”
Section: Introductionmentioning
confidence: 99%